The unique effects of supporting beginning teachers’ psychological needs through learning communities and a teacher-mentor’s support: A longitudinal study based on self-determination theory - Kaplan, Haya (Frontiers in Psychology, 2022)
The induction period is considered one of the most difficult in a teacher’s career. In Israel, support systems for beginning teachers (BTs) include a learning community (LC) and a mentoring process, over a 2-year period. The study was based on self-determination theory and examined how support for BTs’ psychological needs and exploration from the LC facilitator and teacher-mentor contributed to their functioning. The study was conducted over 2 years during which BTs participated in LCs and were accompanied by a teacher-mentor. Questionnaires were administered to Bedouin-Arab and Jewish teachers, 308 interns in the first year, and 205 new teachers in the second. Results of SEM analysis indicated that supporting BTs’ needs and exploration by LC facilitators in both years predicted their autonomous motivation, which in turn predicted positive feelings and satisfaction in the LC. The LC facilitators’ support also predicted the BTs’ autonomous motivation in teaching, which was also predicted by the teacher-mentors’ support. This in turn positively predicted the BTs’ sense of competence and self-actualization, and negatively predicted burnout. In both years, autonomous motivation mediated the association between the support the BTs received, and teacher outcomes in the LC and school. No significant differences were found between the two cultures. The effects found in the second year are above and beyond the effects of support from the LC facilitators and teacher-mentors in the first year. The study indicates the importance of combining multiple induction programs over time and highlights the importance of supporting BTs’ needs during the induction period.